Transparency, Inequity Aversion, and the Dynamics of Peer Pressure in Teams: Theory and Evidence - Mohnen, Alwine; Pokorny, Kathrin; Sliwka, Dirk (Journal of Labor Economics, 2008)
We provide an explanation for peer pressure in teams based on inequity aversion. Analyzing a two‐period model with two agents, we find that the effect of inequity aversion strongly depends on the information structure. When contributions are unobservable, agents act as though they were purely selfish. However, when contributions are made transparent at an interim stage, agents exert higher efforts in the first period and adjust their efforts according to the interim information in the second period. This form of peer pressure reduces free riding, and thus more efficient outcomes are attained. The results are confirmed in a real effort experiment.